Orchiectomy in Medium and Large Dogs - New Surgical Technique - Leal, Leonardo Martins; Rocha, Hagner Alves; Pavilak, Gabriel Aguiar; Gonçalves, Milena Dias; Silveira, Diego Aquino; Romani, Isaac; de Castro Sasahara, Tais Harumi [UNESP]; Moraes, Paola Castro [UNESP] (Universidade Federal do Rio Grande do Sul, 2024)
Background: Castration of males is a surgical procedure, most often elective, being performed in an open or closed way. In small dogs and cats, it is possible to ligate the testicular plexus without the use of surgical thread, causing less local inflammation because there is no exogenous material in the animal. In large patients, this technique has limitations, since because of the greater thickness of the vas deferens duct and vessels, the stitch can loosen and cause trans and postoperative bleeding. The aim of this study was to describe a new orchiectomy technique that dispenses with the use of surgical thread in ligating the testicular arteriovenous plexus in medium and large dogs. Material, Methods & Results: A total of 25 adult dogs, with varied weight (8 a 47 kg), were operated. All animals since study belonged to tutors, coming from clinical consultations in order to perform castration. The entire surgical procedure was properly explained to the owner, as well as all pre-and post-surgical care, for monitoring the animal. All patients were clinically evaluated through anamnesis, physical tests such as palpation and auscultation (cardiac and respiratory) and laboratory tests to discard any animal with systemic changes that made surgery impossible. The breed-wise distribution involved 15 had no defined breed (mixed-breed), followed by 2 Rottweiler, 2 American Bully, 1 Australian Cattle Dog, 1 Labrador, 1 Shih-Tzu, 1 Border Collie, 1 German Shepherd and 1 Pitbull. The average weight was 21.04 kg (ranging between 8 and 47 kg). The beginning of the technique proceeded with the opening of the skin in the pre-scrotal region, with one of the testes positioned below the incision line, to avoid iatrogenic lesions in the urethra. After, the testicular layers were properly incised for exposure of the testicle and posterior ligation of the vessels. Arteriovenous plexus ligation was performed with the aid of a curved hemostatic forceps without the use of surgical thread, using a maneuver similar to making a surgical knot with suture thread, followed by a 360° rotation of the forceps and grasping the plexus. Subsequently, the plexus was sectioned and the vessels slid to complete the ligature. The vas deferens was then ligated using the same technique. The 1st surgery performed on dog 1, from skin incision to dermal synthesis, lasted about 15 min, being noticeable its reduction as the surgeon became familiar with the technique, thus obtaining a surgical time of 5 min in the last patient. The average time to perform the technique was 7'48'' (ranging between 5 and 15 min). Discussion: The advantage of the open technique is that in addition to providing greater visualization of the structures present, as well as direct ligation of blood vessels, reducing the risk of release and consequent bleeding, it allows the knot to be made (with the help of hemostatic forceps) duct and pampiniform plexus in an individualized way. On returning for assessment and subsequent removal of the stitches, it was found that the surgical wounds had healed in all animals. There were no dehiscences, fistulations or bleeding. Seroma was only found in the scrotal region of an animal, similar to what often occurs in the conventional technique, being indicated only medical treatment, with application of cold compresses in the region. The animal returned after 3 days, where the presence of seroma was not observed. These results provide significant contributions that the proposed technique, performed in dogs larger than 5 kg, was safe, fast, easy to perform, low cost and free of severe postoperative complications.
Keywords: canids; castration; hemostatic forceps; veterinary surgery